2007
DOI: 10.1002/ppul.20729
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chronic intermittent and chronic constant hypoxia on postnatal growth and development

Abstract: Summary. Exposure to chronic constant or intermittent hypoxia (CCH or CIH) may have different effects on growth and development in early life. In this work, we exposed postnatal day 2 (P2) CD1 mice to CCH or CIH (11% O 2 ) for 4 weeks and examined the effect of hypoxia on body and organ growth until P30. Regression analysis showed that weight increased in control, CCH and CIH cohorts with age with r 2 values of 0.99, 0.97, and 0.94, respectively. Between days 2 and 30, slopes were 0.93 AE 0.057, 0.76 AE 0.108,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 45 publications
7
49
0
5
Order By: Relevance
“…Weight of rats at the time of weaning (21 days) was 49.53 -3.28 g in those raised under normoxic conditions (NX) and 25.45 -2.12 g in those animals raised at SHA (HX) ( p < 0.0001), as expected from previously reported studies (Farahany et al, 2008;Moore et al, 2011;Chen et al, 2012;Giussani et al, 2012) that showed that chronic hypoxia slows fetal and perinatal growth. Whether these effects are due to different factors, such as neuronal development, endocrine state, and behavior patterns (Peters, 1988;Champagne et al, 2003) or merely represent the known inhibitory effect of hypoxia on body mass, as occurs during later life periods, remains as an open question.…”
Section: Resultssupporting
confidence: 83%
“…Weight of rats at the time of weaning (21 days) was 49.53 -3.28 g in those raised under normoxic conditions (NX) and 25.45 -2.12 g in those animals raised at SHA (HX) ( p < 0.0001), as expected from previously reported studies (Farahany et al, 2008;Moore et al, 2011;Chen et al, 2012;Giussani et al, 2012) that showed that chronic hypoxia slows fetal and perinatal growth. Whether these effects are due to different factors, such as neuronal development, endocrine state, and behavior patterns (Peters, 1988;Champagne et al, 2003) or merely represent the known inhibitory effect of hypoxia on body mass, as occurs during later life periods, remains as an open question.…”
Section: Resultssupporting
confidence: 83%
“…Intestinal weights and lengths and the composition of the intestinal microbiota were not reported. 68 Similar studies have been performed in rats with similar results. 69,70 Attempts to manipulate the intestinal microbiota with probiotics to improve growth in premature infants have been successful in some populations but not in others.…”
Section: Intestinal Microbiota and Probiotics: Potential Role In Termsupporting
confidence: 76%
“…This is starkly contrasted by the extensive literature on intermittent hypoxia in mammals, which has uncovered widespread physiological, developmental and genomic consequences that are distinct from continuous hypoxia exposure (Neubauer, 2001;Douglas et al, 2007;Farahani et al, 2008). There is evidence that exposure to repeated bouts of hypoxia compromises growth in some fish species (Atlantic salmon, Salmo salar, and southern catfish, Silurus meridionalis) but not others (spot, Leiostomus xanthurus, and killifish, Fundulus heteroclitus) (Stierhoff et al, 2003;McNatt and Rice, 2004;Burt et al, 2013;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 49%